A Rapid Colorimetric Assay for On-Site Authentication of Cephalopod Species - Giuseppina Tatulli; Paola Cecere; Davide Maggioni; Andrea Galimberti; Pier Paolo Pompa (Biosensors, 2020)
A colorimetric assay, exploiting the combination of loop-mediated isothermal amplification (LAMP) with DNA barcoding, was developed to address the authentication of some cephalopod species, a relevant group in the context of seafood traceability, due to the intensive processing from the fishing sites to the shelf. The discriminating strategy relies on accurate design of species-specific LAMP primers within the conventional 5’ end of the mitochondrial COI DNA barcode region and allows for the identification of Loligo vulgaris among two closely related and less valuable species. The assay, coupled to rapid genomic DNA extraction, is suitable for large-scale screenings and on-site applications due to its easy procedures, with fast (30 min) and visual readout.